2014
DOI: 10.1080/10705511.2014.919819
|View full text |Cite
|
Sign up to set email alerts
|

Effect Size, Statistical Power, and Sample Size Requirements for the Bootstrap Likelihood Ratio Test in Latent Class Analysis

Abstract: Selecting the number of different classes which will be assumed to exist in the population is an important step in latent class analysis (LCA). The bootstrap likelihood ratio test (BLRT) provides a data-driven way to evaluate the relative adequacy of a (K −1)-class model compared to a K-class model. However, very little is known about how to predict the power or the required sample size for the BLRT in LCA. Based on extensive Monte Carlo simulations, we provide practical effect size measures and power curves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
241
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(245 citation statements)
references
References 57 publications
1
241
0
3
Order By: Relevance
“…Although the profiles differed with regard to levels of self-reported empowering and disempowering coach behaviors, the total number of coaches, particularly in the least empowering profile, was very low. Nevertheless, simulation studies have shown that when the separation between profiles are high (e.g., entropy >.75) sample sizes around 140 is needed to reach sufficient power (Dziak, Lanza, & Tan, 2014;Gudicha, Tekle, & Vermunt, 2016). Given the high entropy in our study it is likely that we have adequate power to find the best solution.…”
Section: Limitationsmentioning
confidence: 98%
“…Although the profiles differed with regard to levels of self-reported empowering and disempowering coach behaviors, the total number of coaches, particularly in the least empowering profile, was very low. Nevertheless, simulation studies have shown that when the separation between profiles are high (e.g., entropy >.75) sample sizes around 140 is needed to reach sufficient power (Dziak, Lanza, & Tan, 2014;Gudicha, Tekle, & Vermunt, 2016). Given the high entropy in our study it is likely that we have adequate power to find the best solution.…”
Section: Limitationsmentioning
confidence: 98%
“…By contrast, a statistically significant LMR-LRT value is indicative of better fit. With the BLRT, this statistic helps to evaluate whether a model improves significantly from the model with k -1 classes, where k is the number of classes for each analysis and there is an assessment as to whether a more parsimonious fit is available (Asparouhov & Muthén, 2012;Dziak, Lanza, & Tan, 2014). The entropy value (i.e.…”
Section: The Process Of Undertaking An Lcamentioning
confidence: 99%
“…Generacijska svijest o specifičnim povijesnim događajima i njihovo iskustvo umnogome se temelji na tome što prenose mediji te na zajedničkim rutinama i upotrebama (informativnih) medija (Westlund i Weibull, 2013: 148). Treba uzeti u obzir i činjenicu da je uzorak na kojem je provedena analiza latentnih klasa razmjerno malen za tu vrstu analize (Diziak, Lanza i Tan, 2014). Zbog toga identificirane klase nisu nužno i najbolja aproksimacija stvarnih medijskih repertoara hrvatskih publika.…”
Section: Zaključakunclassified